A Yb 3+ Doped holmium-based chloride double perovskite material and preparation method and application thereof

Through the YB3+doped oscorion of chloride bisotoxide, combined with the mixing and post -cooling precipitation method, it solves the problem of difficulty obtaining the transformation of doped doped doped twin oscomority. Performance and near -infrared quantum tailoring is suitable for a variety of high -tech fields.

CN117070221BActive Publication Date: 2025-01-28WUHAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310937826.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-26
Publication Date
2025-01-28
Estimated Expiration
2043-07-26

AI Technical Summary

Technical Problem

Existing lanthanide-doped biperovskite upconversion luminescent materials are difficult to obtain, and their optical properties are mainly concentrated on photoluminescence phenomena that follow Stokes' law, lack of multi-color upconversion luminescent properties and regulation of activator concentration. abilities research.

Method used

Using YB3+doped osteothalinosol (CS2NAHO1-XYBXCL6), through rare earth ion ion mixing, combined with the cooling and precipitation synthetic material through rare earth ion ingot, and the light transformation performance on multi-color, and by adjusting the concentration of YB3+ions, Regulate the color of glow.

Benefits of technology

Achieve the modulation from red to orange to green under 980nm laser, and converts the red emission to 980nm near -infrared launch under 450nm. It has high -efficiency transformation fluorescent adjustability. It is suitable for optoelectronic devices and information security. , Biological probes and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117070221B_ABST
    Figure CN117070221B_ABST
Patent Text Reader

Abstract

The present invention discloses a Yb 3+ Doped holmium-based chloride double perovskite material and preparation method and application thereof. 3+ The chemical formula of the holmium-doped chloride double perovskite material is: Cs2NaHo 1‑ x Yb x Cl6; wherein 1%≤x≤99%. The present invention uses rare earth ion ytterbium doping to make Yb 3+ The doped lead-free double perovskite has the ability of upconversion luminescence. 3+ ‑Yb 3+ The efficient quantum cutting effect between Cs2NaHo 1‑x Yb x Under 450nm excitation, Cl6 microcrystals no longer produce red emission from the matrix itself but are converted into efficient near-infrared emission at 980nm. They have near-infrared quantum tailored emission and up-conversion fluorescence adjustability, and have certain promotion value in the fields of optoelectronic devices, information security, biological probes, sensors, lasers, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of rare earth luminescent materials, in particular to a Yb 3+ Doped holmium-based chloride double perovskite material, preparation method and application thereof. Background Art

[0002] In recent years, lead halide perovskites (APbX3, X = Cl, Br, I) have attracted great attention in the fields of solar cells, light-emitting diodes (LEDs), photodetectors, etc. due to their advantages such as high carrier mobility, adjustable band gap, and large absorption coefficient. However, the toxicity of lead ions and their own hygrothermal instability have become a huge obstacle to practical applications. Lead-free halide double perovskites (A2mMX6) are synthesized by using a trivalent metal cation M 3+ With a monovalent metal cation m + Replace two Pb 2+ It solves the toxicity problem of lead-based perovskites while maintaining the overall charge balance and perovskite structure, and has a high defect tolerance and an octahedral environment suitable for trivalent rare earth doping, making it an ideal matrix for rare earth doping.

[0003] However, most reported double perovskite host materials are based on trivalent main-group metal ions, including Sb 3+ 、Bi 3+ andIn 3+ Lanthanide doping is one of the means to adjust the luminescence properties of double perovskite materials, but due to the same main element (Sb 3+ 、Bi 3+ andIn 3+ (etc.) The ion radius of the lanthanide is very different, which usually causes lattice mismatch. And the actual doping amount of lanthanide elements is very small, which often causes weak characteristic emission due to low energy transfer efficiency or luminescence quenching due to excessive concentration. In addition, people have always focused on the photoluminescence phenomenon that follows Stokes' law for the optical properties of lanthanide-doped double perovskite materials, that is, obtaining visible light or even near-infrared light through ultraviolet or deep ultraviolet excitation, and rarely pay attention to its upconversion luminescence performance. The development of multicolor upconversion emission may have revolutionary applications in a wide range of research fields, including complex data analysis, information storage, biosensors, laser emitters, etc. In addition, cross relaxation (CR) between upconversion luminescence activators is generally considered to be harmful, so its ability to regulate upconversion red emission is often overlooked. As far as we know, the concentration of activators in lanthanide-doped upconversion materials is usually limited to less than 2 mol% to reduce CR, and there is almost no systematic study on the upconversion behavior of a large number of activators. Summary of the invention

[0004] The purpose of the present invention is to overcome the above technical deficiencies and provide a Yb 3+ The invention discloses a holmium-doped chloride double perovskite material and a preparation method and application thereof, which solve the technical problem that lanthanide-doped double perovskite upconversion luminescent materials are difficult to obtain in the prior art.

[0005] In the first aspect, the present invention provides a Yb 3+ Doped holmium-based chloride double perovskite materials, the Yb 3+ The chemical formula of the holmium-doped chloride double perovskite material is: Cs2NaHo 1-x Yb x Cl6; wherein 1%≤x≤99%.

[0006] In a second aspect, the present invention provides a Yb 3+ The preparation method of the doped holmium-based chloride double perovskite material comprises the following steps:

[0007] Adding a sodium source, a holmium-containing compound and an ytterbium-containing compound into concentrated hydrochloric acid, and stirring at 75 to 80° C. until they are completely dissolved, to obtain a clear precursor solution; wherein the molar ratio of Na to (Ho+Yb) is (0.75 to 0.85):1;

[0008] The reaction temperature of the clarified precursor solution is lowered by 5 to 10° C. to obtain a supersaturated precursor solution;

[0009] Cesium chloride was added to the supersaturated precursor solution for precipitation reaction. After the reaction was completed, it was naturally cooled to room temperature, and Yb was obtained by centrifugal washing and drying. 3+ Doped holmium-based chloride double perovskite materials.

[0010] In a third aspect, the present invention provides the above-mentioned Yb 3+ Application of holmium-doped chloride double perovskite materials as up-conversion luminescent materials, down-conversion luminescent materials, and near-infrared quantum tailored luminescent materials.

[0011] Compared with the prior art, the beneficial effects of the present invention include:

[0012] (1) The holmium-based double perovskite material Cs2NaHoCl6 of the present invention has an extremely wide absorption band, and the band edge absorption can reach around 550nm. Under the irradiation of ultraviolet light and short-wave blue light (450nm), self-trapped exciton emission and Ho-based 3+ ff's radiative transition red emission; under 450nm blue light excitation, the luminescence quantum efficiency (PLQY) can reach 17.45%, which is suitable for commercial low-cost 450nm LED chips and can be promoted as a high-efficiency blue-light-excited red LED powder.

[0013] (2) The present invention uses rare earth ion ytterbium doping to make Yb3+ The doped lead-free double perovskite has the ability of up-conversion luminescence. Under the low concentration of 1% Yb ion doping, the material shows obvious red emission under 980nm laser; under the medium concentration of 5-10% Yb ion doping, the material shows obvious orange emission under 980nm laser; under the higher concentration of 20% or more Yb ion doping, the material shows green emission under 980nm laser. 3+ -Yb 3+ The efficient quantum cutting effect between Cs2NaHo 1-x Yb x When excited at 450nm, Cl6 microcrystals no longer produce red emission from the matrix itself but are converted into efficient near-infrared emission at 980nm.

[0014] (3) The present invention uses a post-cooling precipitation method to synthesize Cs2NaHo 1-x Yb x Cl6 microcrystalline material has simple process, good cost control, and is suitable for large-scale preparation. The synthesized material has stable phase, pure luminescent chromaticity, and adjustable upconversion luminescence.

[0015] (4) Cs2NaHo of the present invention 1-x Yb x Cl6 microcrystalline material is a multicolor upconversion luminescent material with good stability in air and light. It can be used in optoelectronic devices, information security, biological probes, sensors, lasers and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Cs2NaHo 1-x Yb x Crystal structure diagram of Cl6 microcrystalline material;

[0017] Figure 2 Cs2NaHo prepared in Examples 1 to 5 1-x Yb x X-ray diffraction patterns (XRD) of Cl6 microcrystalline material and Cs2NaHoCl6 microcrystalline material prepared in Comparative Example 1;

[0018] Figure 3 The scanning electron microscope (SEM) and energy dispersive spectrometer (EDS) of Cs2NaHoCl6 prepared in Comparative Examples 1 and 2;

[0019] Figure 4 Cs2NaHo prepared in Example 5 1-x Yb xScanning Electron Microscope (SEM) and Energy Dispersive Spectrometer (EDS) of Cl6 microcrystalline materials;

[0020] Figure 5 Cs2NaHo prepared in Example 4 1-x Yb x X-ray photoelectron spectroscopy (XPS) of Cl6 microcrystalline material and Cs2NaHoCl6 microcrystalline material prepared in Comparative Example 1;

[0021] Figure 6 Absorption spectrum, excitation spectrum and emission spectrum of Cs2NaHoCl6 microcrystalline material prepared in Comparative Example 1;

[0022] Figure 7 Cs2NaHo prepared in Examples 1, 2 and 5 1-x Yb x Upconversion luminescence (UPL) spectra of Cl6 microcrystalline materials and Cs2NaHo prepared in Examples 1, 2, 3, 5, 6, and 7 1-x Yb x Comparison chart of red-green intensity ratio of upconversion luminescence spectrum of Cl6 microcrystalline material;

[0023] Figure 8 Cs2NaHo prepared in Examples 1, 2, 3, 5, 6, and 7 1-x Yb x Upconversion luminescence (UPL) spectrum of Cl6 microcrystalline material; the arrow direction on the left is 90%, 1%, 5%, 10%, 50%, 20% in sequence, and the arrow direction on the right is 90%, 50%, 10%, 5%, 1%, 20% in sequence;

[0024] Fig. 9 Cs2NaHo prepared in Examples 2 to 5 1-x Yb xThe down-conversion spectra and fluorescence lifetime spectra (Fluorescence Lifetime Spectrum) of Cl6 microcrystalline material and Cs2NaHoCl6 microcrystalline material prepared in comparative example 1 in the visible light and near-infrared light regions under 450nm excitation; wherein, along the direction of the arrows, they are 0%, 5%, 10%, 15%, and 20% respectively. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0026] In the first aspect, the present invention provides a Yb 3+ Doped holmium-based chloride double perovskite materials, the Yb 3+ The chemical formula of the holmium-doped chloride double perovskite material is: Cs2NaHo 1-x Yb x Cl6; wherein 1%≤x≤99%, including but not limited to 1%, 2%, 5%, 10%, 15%, 20%, 25%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 99%, etc.

[0027] The Yb provided by the present invention 3+ In the doped holmium-based chloride double perovskite material, the matrix used - holmium-based chloride double perovskite (Cs2NaHoCl6) microcrystalline material, adopts monovalent Na + Ions and trivalent Ho 3+ ions to replace two Pb 2+ , while maintaining the total charge balance and perovskite structure, the toxicity problem of lead-based perovskites is solved. At the same time, the base material (Cs2NaHoCl6) does not have the lattice mismatch and low energy transfer efficiency or concentration quenching caused by concentration that may occur in the perovskite lattice of lanthanides. In addition, the matrix material (Cs2NaHoCl6) retains the hexacoordination environment of traditional perovskites that is very suitable for doping with trivalent lanthanides. At the same time, the lanthanide element Ho is used as the main element. Due to the similar physical and chemical properties, it will be more conducive to the doping and substitution of other lanthanides, reducing the occurrence of lattice mismatch, weak characteristic emission and other problems. Therefore, Ho 3+ Ions play two roles in this structure: as an extremely stable perovskite host lattice, and provide two emission centers, self-trapped excitons and lanthanide ions, which can be promoted as a promising optoelectronic material. The matrix material (Cs2NaHoCl6) also has the characteristics of low phonon energy, low toxicity, and excellent thermal stability. The preparation process is simple and easy to promote industrialization. It can be used as an excellent candidate material for upconversion matrix.

[0028] The present invention adopts the method of doping sensitizing ion Yb 3+ Preparation of Cs2NaHo 1-x Yb x Cl6 microcrystalline material has obtained extremely excellent multi-color up-conversion luminescence performance. Under low concentration 1% Yb ion doping, the material shows obvious red emission under 980nm laser; under medium concentration 5% to 10% Yb ion doping, the material shows obvious orange emission under 980nm laser; under higher concentration 20% or more Yb ion doping, the material shows green emission under 980nm laser. In this process, Ho 3+ There is a good metastable energy level, which can ensure the generation of red and green emission; while Yb 3+ The ion has a simple and unique energy level structure (the 4f layer has only two energy levels 2 F 7 / 2 Ground state and 2 F 5 / 2 Excited state), there is strong absorption between the two energy levels near 980nm, and the same as Ho 3+ The considerable energy match between the emission levels of Cs2NaHo 1-x Yb x Cl6 to become an efficient 980nm near-infrared excitation sensitizer. 3+ As the main element and in the presence of a large amount of activators, a multicolor upconversion emitting material is obtained. This strategy based on the CR effect not only successfully achieves the modulation of very pure red upconversion emission to green upconversion emission (the red-green light intensity ratio can be spanned from 0.14 to as high as 12.5 or more), but can also be used as an alternative method for precise upconversion color adjustment and provide further insights into the upconversion luminescence mechanism. At the same time, the Yb provided by the present invention 3+ The holmium-doped chloride double perovskite material has near-infrared emission performance around 980nm under 450nm excitation.

[0029] In a second aspect, the present invention provides a Yb 3+ The preparation method of the doped holmium-based chloride double perovskite material comprises the following steps:

[0030] S1. Add the sodium source, the holmium-containing compound and the ytterbium-containing compound into concentrated hydrochloric acid and stir at 75-80° C. until they are completely dissolved to obtain a clear precursor solution.

[0031] S2. Lower the reaction temperature of the clarified precursor solution by 5 to 10° C. to obtain a supersaturated precursor solution. During this process, the temperature must be strictly controlled. If the temperature is lowered too much, sodium chloride crystals will precipitate. If the temperature is not lowered, the yield will be too low or precipitation will not be possible.

[0032] S3, adding cesium chloride to the supersaturated precursor solution for precipitation reaction, cooling naturally to room temperature after the reaction is complete, washing by centrifugation, and drying to obtain Yb 3+ Doped holmium-based chloride double perovskite materials.

[0033] The present invention also provides a method for quickly and easily preparing Yb 3+ Method for doping holmium-based chloride double perovskite materials. The preparation method of traditional lanthanide-based perovskite (Cs2NaLnCl6, Ln = lanthanide element) microcrystals requires that the original lanthanide oxide and sodium source powder be placed in a silicon tube in a vacuum, and these silicon tubes are calcined at a high temperature of 850°C in a Brigman furnace to obtain agglomerated Cs2NaLnCl6 products. This method has extremely high requirements on the anhydrous degree of the raw materials, usually requiring 99.99% of lanthanide oxides (anhydrous grade lanthanide compounds, which are extremely expensive), and has high energy consumption and poor product morphology as a solid solution. At the same time, although the precipitation method is a commonly used method for preparing traditional double perovskites, it is not ideal for the preparation of lanthanide-based perovskites, and often does not precipitate, so there are no related reports. The inventors have improved the precipitation method and creatively proposed to add a sodium source, a holmium-containing compound and an ytterbium-containing compound to a chloride ion-rich environment of concentrated hydrochloric acid, obtain a supersaturated precursor solution by lowering the temperature, and reduce the Na + Same as Ho 3+ +Yb 3+ The molar ratio of is about 0.8 to promote the precipitation reaction. The preparation method provided by the present invention does not require strict anhydrous grade lanthanide compounds, and the preparation conditions can be met by using low-cost hexahydrate holmium chloride HoCl3·6H2O or other holmium sources. The reaction temperature of the present invention is low (below 80°C), which can be achieved by general heating means, with low energy consumption, simple operation, and convenient for industrial production and promotion. It can be applied to the preparation of other lanthanide-based perovskite (Cs2NaLnCl6, Ln = lanthanide element) microcrystalline materials.

[0034] In this embodiment, in step S1, the sodium source is at least one of sodium chloride, sodium hydroxide, sodium carbonate or sodium bicarbonate, preferably sodium chloride; the holmium-containing compound is at least one of holmium chloride, holmium oxide and holmium carbonate, preferably holmium chloride; the ytterbium-containing compound is at least one of ytterbium chloride, ytterbium oxide and ytterbium carbonate, preferably ytterbium chloride. Those skilled in the art should understand that the above compounds all include their hydrate forms.

[0035] In this embodiment, in step S1, the mass fraction of concentrated hydrochloric acid is 36-38%, and the ratio of cesium chloride to concentrated hydrochloric acid is 1mmol: (1.8-2.2)ml, further 1mmol: 2ml. If the amount of concentrated hydrochloric acid is too much, it will be difficult to form a saturated solution. If the amount of concentrated hydrochloric acid is too little, it will require a higher temperature and time to dissolve the relevant salts, increasing energy consumption.

[0036] In the present embodiment, the molar ratio of Cs to (Ho+Yb) is (1.8-2.2):1, preferably 2:1.

[0037] In this embodiment, the molar ratio of Na to (Ho+Yb) is (0.75-0.85):1. Within this molar ratio range, a relatively pure crystalline sample can be obtained. When the NaCl ratio is too high, the product contains NaCl byproducts precipitated due to cooling; when the NaCl ratio is too low, it is not conducive to the occurrence of precipitation reaction. The molar ratio of Na to (Ho+Yb) is preferably 0.8:1.

[0038] In this embodiment, in step S1, the time required for stirring until complete dissolution is 0.5 to 2 hours.

[0039] In this embodiment, in step S2, the precipitation reaction is carried out under stirring; the precipitation reaction time is 10 to 60 minutes, further 20 to 40 minutes.

[0040] In this embodiment, in step S3, the centrifugal speed is 4000-7000 rpm; the washing solvent is anhydrous ethanol or methanol, the washing times are 3-5 times, and the centrifugal time for each time is 3-5 minutes; the drying temperature is 60-80°C, and the drying time is more than 12 hours. The drying time should be as long as possible to ensure the removal of crystal water and free water. Usually, 1 mmol of the product needs to be dried at 80°C for 12 hours to obtain a dry and loose white powder sample Cs2NaHo 1-x Yb x At the same time, in order to avoid the formation of crystal water due to the strong hydrophilicity of lanthanide ions, it needs to be sealed and stored in a dry silicon ball or vacuum box.

[0041] In a third aspect, the present invention provides the above-mentioned Yb 3+ Application of holmium-doped chloride double perovskite materials as up-conversion luminescent materials, down-conversion luminescent materials, and near-infrared quantum tailored luminescent materials.

[0042] In this embodiment, the above Yb 3+ Doped holmium-based chloride double perovskite materials are used in optoelectronic devices, information security, biological probes, sensors, and lasers.

[0043] Example 1

[0044] Theoretical Cs2NaHo 0.99 Yb 0.01Preparation of Cl6 microcrystalline material: weigh 0.40mmol NaCl, 0.495mmol HoCl3·6H2O and additional 0.005mmol YbCl3·6H2O, add to 2ml 37% concentrated hydrochloric acid, stir at 78℃ for 1h until completely dissolved, then cool to 68℃, add 1mmol CsCl powder, and the powder will precipitate. As the stirring proceeds, the precipitate gradually increases. Keep stirring for half an hour, cool naturally to room temperature, and then centrifuge and wash three times. Add 15ml ethanol each time and shake for 30 seconds, then put into a centrifuge and centrifuge at 6000rpm for 4 minutes; after washing, put into an oven, dry at 80℃ for 12h, and then take out to obtain a microcrystalline material with a Yb / (Ho+Yb) source filler ratio of 1%.

[0045] Embodiments 2 to 8

[0046] The preparation process of Examples 2 to 8 is the same as that of Example 1, the only difference being the amount of raw materials used, as shown in Table 1.

[0047] Table 1 Component addition amount of each sample and actual proportion of rare earth

[0048]

[0049]

[0050] As can be seen from Table 1, the obtained samples were subjected to inductively coupled plasma mass spectrometry (ICP) test, indicating that Yb 3+ The actual ion doping amount is basically consistent with the theoretical filling ratio.

[0051] Also, see Figure 1 , Figure 1 Cs2NaHo 1-x Yb x Crystal structure diagram of Cl6 microcrystalline material. Figure 1 The lattice structure shown, [NaCl6] 5- and [HoCl6] 3- The octahedrons form a perovskite structure in a corner-sharing manner, in which the doped Yb 3+ Ion replacement of some Ho 3+ position and enter the lattice.

[0052] Comparative Example 1

[0053] Preparation of Cs2NaHoCl6 microcrystalline material: weigh 0.40mmol NaCl and 0.5mmol HoCl3·6H2O, add them into 2ml37% concentrated hydrochloric acid, stir at 78℃ for 1h until the chloride is completely dissolved, then cool to 68℃, add 1mmol CsCl powder into the supersaturated sodium salt precursor solution, and the powder will precipitate. As the stirring proceeds, the precipitate gradually increases. After stirring for half an hour, cool naturally to room temperature, and then centrifuge and wash three times. Add 15ml ethanol each time, shake for 30 seconds, put into centrifuge, and centrifuge at 6000rpm for 4 minutes; after washing, put into oven, dry at 80℃ for 12h, and then take out to obtain Cs2NaHoCl6 product.

[0054] Comparative Example 2

[0055] Preparation of Cs2NaHoCl6 microcrystalline material: weigh 0.60mmol NaCl and 0.5mmol HoCl3·6H2O and add them to 2ml37% concentrated hydrochloric acid, stir at 78°C until the holmium chloride crystals are completely dissolved, but when chloride salt crystals still remain, quickly add 1mmol CsCl powder to it and precipitate. Take it out immediately and cool it to room temperature, then centrifuge and wash three times, add 15ml ethanol each time and shake for 30 seconds, then put it into a centrifuge and centrifuge it at 6000rpm for 4 minutes; after washing, put it into an oven, dry it at 80°C for 12h, and then take it out to obtain a powder sample.

[0056] Experimental Group 1

[0057] Cs2NaHo 1-x Yb x XRD test of Cl6 microcrystalline material

[0058] See also Figure 2 , Figure 2 Cs2NaHo prepared in Examples 1 to 5 1-x Yb x X-ray diffraction patterns (XRD) of Cl6 microcrystalline material and Cs2NaHoCl6 microcrystalline material prepared in Comparative Example 1. Figure 2 As shown, Cs2NaHo with different Yb doping 1-x Yb x Cl6 microcrystalline materials all have the crystal structure characteristics of perovskite and crystallize in the cubic Fm-3m space group. At the same time, the XRD peaks of the systems before and after doping are basically the same, indicating that they maintain the same crystal structure. The enlarged spectrum at 23°-24° shows that with the increase of Yb 3+ The increase of ion concentration has the characteristic of slight shift of diffraction peak to larger angle, which comes from the higher Ho 3 +Yb with a smaller ionic radius 3+ The lattice shrinkage caused by the introduction of Yb is shown in Table 1. 1% to 20% refers to the Yb / (Ho+Yb) source filling ratio during sample preparation.

[0059] Experimental Group 2

[0060] For Cs2NaHoCl6 and Cs2NaHo 1-x Yb x Cl6 microcrystalline material was tested by SEM and EDS

[0061] See also Figure 3 , Figure 3 The scanning electron microscope (SEM) and energy dispersive spectrometer (EDS) images of Cs2NaHoCl6 prepared in Comparative Examples 1-2 are shown. Figure 3 (a) is the Cs2NaHoCl6 microcrystalline material prepared in Comparative Example 1. From SEM, it can be observed that the Cs2NaHoCl6 tends to be octahedral crystallized and belongs to the cubic phase Fm-3m space group; and the EDS energy spectrum shows that the elements are evenly distributed without enrichment. Figure 3 (b) is the sample powder prepared in Comparative Example 2. No octahedral crystals can be observed from SEM, that is, no Cs2NaHoCl6 microcrystals with good crystallinity can be found, but the presence of cubic sodium chloride crystals can be clearly observed, and the EDS spectrum reveals that the particles attached to and scattered beside the sodium chloride crystals are likely to be Cs2NaHoCl6 twins with extremely poor crystallinity. In addition, the addition of excessive NaCl, too low heating temperature, short stirring time, and insufficient reaction time may all lead to this situation, which is not conducive to the preparation of Cs2NaHoCl6 microcrystalline materials. 1-x Yb x The same rules also exist in the preparation process of Cl6 microcrystalline materials.

[0062] See also Figure 4 , Figure 4 Cs2NaHo prepared in Example 5 1-x Yb x Scanning Electron Microscope (SEM) and Energy Dispersive Spectrometer (EDS) of Cl6 microcrystalline materials. Figure 4 As shown, Cs2NaHo prepared in Example 5 1-x Yb xCl6 microcrystalline material has the characteristics of randomly stacked octahedral crystals with a particle size of about 3-8 microns; EDS scanning of scattered crystals shows that the signal only has Cs, Na, Ho, Cl, and Yb element signals, and the distribution is uniform without aggregation, which further proves that Cs2NaHo 1-x Yb x Successful synthesis of Cl6 microcrystals.

[0063] Experimental Group 3

[0064] Cs2NaHo 1-x Yb x XPS test of Cl6 microcrystalline material

[0065] See also Figure 5 , Figure 5 Cs2NaHo prepared in Example 4 1-x Yb x X-ray photoelectron spectroscopy (XPS) of Cl6 microcrystalline material and Cs2NaHoCl6 microcrystalline material prepared in Comparative Example 1. Figure 5 As shown in (a), the Cs2NaHoCl6 microcrystalline material prepared in Comparative Example 1 + 、Na + 、Ho 3+ , Cl - The binding energy peak is obvious; Cs2NaHo prepared in Example 4 0.86 Yb 0.14 Cl6 (expressed as measured value) has an additional Yb binding energy peak compared to the original Cs2NaHoCl6; Figure 5 As shown in (b), Yb appears in the Yb-doped material. 3+ The binding energy peaks are 186.5 eV for Yb 4 d 5 / 2 and 190.9 eV Yb 4 d 3 / 2 , indicating that the Yb element successfully enters the perovskite lattice in a trivalent state, further illustrating the successful synthesis and composition regulation of the material.

[0066] Experimental Group 4

[0067] Absorption, excitation and emission spectra of Cs2NaHoCl6 microcrystalline materials

[0068] See also Figure 6 , Figure 6The absorption spectrum, excitation spectrum and emission spectrum of the Cs2NaHoCl6 microcrystalline material prepared in Comparative Example 1 are shown in FIG. Figure 6 As shown in (a), there are multiple absorption peaks from 300nm to 600nm. The three absorption peaks before 450nm belong to the self-trapped exciton absorption of the perovskite and its dark exciton absorption. The absorption peaks at 450nm and 460nm are Ho 3+ ff transition absorption peak. Under the excitation of 362nm and 450nm xenon lamps, it shows bright red emission with a peak at 656nm. Figure 6 As shown in (b), the absorption peak of the self-trapped exciton at 322nm is used to excite the self-trapped exciton, showing a broad self-trapped exciton emission and a Ho at 656nm. 3+ Characteristic emission peaks.

[0069] Experimental Group 5

[0070] Cs2NaHo 1-x Yb x Cl6 microcrystalline material up-conversion luminescence spectrum test

[0071] See also Figure 7 and 8 , Figure 7 (a), (b), (c) are Cs2NaHo prepared in Examples 1, 2 and 5 1-x Upconversion luminescence (UPL) spectrum of YbxCl6 microcrystalline material. Figure 7 (a), (b), and (c) show that under 980nm laser excitation, different Cs2NaHo 1-x Yb x Cl6 has three fluorescence peaks in the visible light band, located at 490nm, 550nm, and 656nm, corresponding to Ho 3+ Ionic 5 F3, 5 F4 / 5 S2 and 5 F5 energy level to baseband 5 The ratio of the green peak at 550nm and the red peak at 656nm depends on the concentration of Yb ions. 0.99 Yb 0.01 Cl6 shows red luminescence ( Figure 7 (a)), Cs2NaHo 0.95 Yb 0.05 Cl6 shows orange luminescence ( Figure 7 (b)), Cs2NaHo0.8 Yb 0.2 Cl6 exhibits green luminescence ( Figure 7 (c)). Figure 7 As shown in (d), without Yb doping, the sample shows almost no upconversion luminescence properties. After trace doping with Yb, the upconversion luminescence performance is greatly improved, and the fluorescence intensity is increased by about 50 times. At the same time, the red and green light modulation of the material is extremely efficient, such as Figure 7 As shown in (e), by controlling the Yb content, a wide range of luminescence modulation can be obtained, with the red-green intensity ratio ranging from 0.14 to 12.5, and very pure red and green light emission can be achieved. Figure 8 , Figure 8 Cs2NaHo prepared in Examples 1, 2, 3, 5, 6, and 7 1-x Yb x Upconversion luminescence (UPL) spectrum of Cl6 microcrystalline material. Figure 8 As shown, under 980nm laser excitation, Cs2NaHo with different Yb doping 1-x Yb x All Cl6 microcrystalline materials have up-conversion luminescence properties.

[0072] Experimental Group 6

[0073] Cs2NaHo 1-x Yb x Visible light spectrum, infrared emission spectrum and fluorescence lifetime test of Cl6

[0074] See also Fig. 9 , Fig. 9 Cs2NaHo prepared in Examples 2 to 5 1-x Yb x Down-conversion spectra and fluorescence lifetime spectra of the Cl6 microcrystalline material and the Cs2NaHoCl6 microcrystalline material prepared in Comparative Example 1 in the visible light and near-infrared light regions under 450nm excitation. Fig. 9 As shown in (a), under a 450nm xenon lamp, the 656nm emission of Cs2NaHoCl6 is converted to Yb due to quantum clipping. 3+ It emits efficiently in the infrared band of 980nm. Fig. 9 (b) and 9(c) show that the energy migration is as high as 99.56% before and after doping. 3+ of 5 F5- 5 I8 and Yb 3+ of 2 F 5 / 2 -2 F 3 / 2 There is efficient energy transfer between them, which further reveals that Cs2NaHo 1-x Yb x Energy transfer process between Ho and Yb ions in Cl6.

[0075] In summary, the present invention is to activate the ion Ho 3+ As the main element of lead-free double perovskite, the sensitizing ion Yb 3+ A simple precipitation method was used to synthesize Yb 3+ Doped holmium-based chloride double perovskite materials (Cs2NaHo 1- x Yb x Cl6). The Cs2NaHo 1-x Yb x Cl6 has excellent concentration-dependent upconversion luminescence properties, and can achieve modulation from red upconversion luminescence to orange upconversion luminescence and then to green upconversion luminescence under 980nm laser; at the same time, Cs2NaHo 1-x Yb x Under 450nm excitation, Cl6 can convert almost all of the red emission of Cs2NaHoCl6 at 656nm into near-infrared emission at 980nm. It has near-infrared quantum tailored emission and upconversion fluorescence adjustability, and has certain promotion value in optoelectronic devices, information security, biological probes, sensors, lasers and other fields.

[0076] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A Yb 3+ The method for preparing a doped holmium-based chloride double perovskite material is characterized in that: The Yb 3+ The chemical formula of the holmium-doped chloride double perovskite material is: Cs2NaHo 1-x Yb x Cl6, 1%≤x≤99%; the preparation method comprises the following steps: Adding a sodium source, a holmium-containing compound and an ytterbium-containing compound into concentrated hydrochloric acid and stirring at 75-80° C. until they are completely dissolved, to obtain a clear precursor solution; wherein the molar ratio of Na to (Ho+Yb) is (0.75-0.85):1; The reaction temperature of the clarified precursor solution is lowered by 5-10°C to obtain a supersaturated precursor solution; Cesium chloride was added to the supersaturated precursor solution for precipitation reaction. After the reaction was completed, it was naturally cooled to room temperature, and Yb was obtained by centrifugal washing and drying. 3+ Doped holmium-based chloride double perovskite material; wherein, The mass fraction of the concentrated hydrochloric acid is 36-38%, and the dosage ratio of the cesium chloride to the concentrated hydrochloric acid is 1 mmol: (1.8-2.2) ml; The molar ratio of Na to (Ho+Yb) is 0.8:1; The precipitation reaction is carried out under stirring; the precipitation reaction time is 10 to 60 min.

2. According to claim 1, Yb 3+ The method for preparing a doped holmium-based chloride double perovskite material is characterized in that: The usage ratio of cesium chloride to concentrated hydrochloric acid is 1 mmol:2 ml.

3. Yb according to claim 1 3+ The method for preparing a doped holmium-based chloride double perovskite material is characterized in that: The molar ratio of Cs to (Ho+Yb) is (1.8~2.2):

1.

4. According to claim 3, Yb 3+ The method for preparing a doped holmium-based chloride double perovskite material is characterized in that: The molar ratio of Cs to (Ho+Yb) is 2:

1.

5. Yb according to claim 1 3+ The method for preparing a doped holmium-based chloride double perovskite material is characterized in that: The sodium source is at least one of sodium chloride, sodium hydroxide, sodium carbonate or sodium bicarbonate; the holmium-containing compound is at least one of holmium chloride, holmium oxide and holmium carbonate; the ytterbium-containing compound is at least one of ytterbium chloride, ytterbium oxide and ytterbium carbonate.